Physiological and molecular mechanism of ginger (Zingiber officinale Roscoe) seedling response to salt stress - Liu, Miaohong; Lv, Yao; Cao, Bili; Chen, Zijing; Xu, Kun (Frontiers in Plant Science, 2023)
Today's agricultural production faces significant challenges from salinization, and salt stress has developed into a significant abiotic stressor restricting growth worldwide. We used ‘Shannong No.1’ as experimental material to simulate the higher salt concentration of ginger, and we analyzed the physiological responses of the different parts (root, stem, leaf, and rhizome) of ginger seedlings under salt stress to specify the reaction of ginger seedlings to salt tolerance. The root and leaf were the parts with the most significant variation, according to our analysis and measurement of the alterations in physiological indices, including the growth index, osmotic system, and antioxidant system. After 80 days of planting, we used RNA-seq to analyze transcriptional differences in the root and leaf of ginger. GO enrichment and KEGG signaling pathway enrichment were then carried out using the findings of the RT-qPCR analysis, and differential genes were chosen and verified. The response of different tissues and parts of ginger to salt stress in the seedling stage was elucidated by combining physiological and molecular indexes.